Differential Cellular and Molecular Effects of Butyrate and Trichostatin A on Vascular Smooth Muscle Cells - Kasturi Ranganna; Frank M. Yatsu; Omana P. Mathew; Shirlette G. Milton (MDPI AG, 2012)
The histone deacetylase (HDAC) inhibitors, butyrate and trichostatin A (TSA), are epigenetic histone modifiers and proliferation inhibitors by downregulating cyclin D1, a positive cell cycle regulator, and upregulating p21Cip1 and INK family of proteins, negative cell cycle regulators. Our recent study indicated cyclin D1 upregulation in vascular smooth muscle cells (VSMC) that are proliferation-arrested by butyrate. Here we investigate whether cyclin D1 upregulation is a unique response of VSMC to butyrate or a general response to HDAC inhibitors (HDACi) by evaluating the effects of butyrate and TSA on VSMC. While butyrate and TSA inhibit VSMC proliferation via cytostatic and cytotoxic effects, respectively, they downregulate cdk4, cdk6, and cdk2, and upregulate cyclin D3, p21Cip1 and p15INK4B, and cause similar effects on key histone H3 posttranslational modifications. Conversely, cyclin D1 is upregulated by butyrate and inhibited by TSA. Assessment of glycogen synthase 3-dependent phosphorylation, subcellular localization and transcription of cyclin D1 indicates that differential effects of butyrate and TSA on cyclin D1 levels are linked to disparity in cyclin D1 gene expression. Disparity in butyrate- and TSA-induced cyclin D1 may influence transcriptional regulation of genes that are associated with changes in cellular morphology/cellular effects that these HDACi confer on VSMC, as a transcriptional modulator.